Advances in the Diagnosis and Management of Uveitis - Rodriguez-Garcia, Alejandro; Stephen Foster, C. (IntechOpen, 2019)
Uveitis is the fifth cause of visual loss in the developed world, accounting for up to 20% of legal blindness. Visual loss due to uveitis currently has a significant impact on the productivity and quality of life of many patients worldwide. Therefore, advances in diagnostic techniques and therapeutic strategies are crucial for patients suffering from the disease. Improvements in our understanding of the pathogenic mechanisms, development of more accurate diagnostic tests, and better treatment alternatives come from the continuous efforts of researchers from all over the world who are committed to improving the standard of care of patients suffering from these potentially blinding diseases.This book focuses on the most recent advances in diagnostic techniques for primary and systemic-associated autoimmune and infectious uveitis, as well as new therapeutic strategies that have significantly reduced the rate of ocular complications and improved the visual outcome of patients suffering from these devastating disorders.